Functional Assessment of Congenital Radioulnar Synostosis in Children - Moghamis, Isam Sami; Abuhejleh, Hasan; Abuodeh, Yousef; Nasef, Hazem Mohamad; Thanaraj, Harris Manova; Preez, Ilse Du; Kawas, Mohamad Alaa (Avicenna Journal of Medicine, 2025)
Background Congenital radioulnar synostosis (CRUS) is a rare condition caused by segmentation failure in embryonic life. The forearm is usually fixed in pronation, affecting the upper limb and hand functions. Treatment ranges from observation to surgical options to restore limb function and prevent disease recurrence. The study aimed to assess the functional outcome of patients with CRUS.Methods We conducted a prospective evaluation of eight patients with CRUS between 2010 and 2020. The data involved history, physical examination, and functional assessment using the ABILHAND-Kids functional scale to determine children's adaptation to this deformity and the indication for surgical management. A control sample of four patients was included in the study for comparison.Results Eight patients with 11 limb deformities were included in the study. The affected limbs' range of motion (ROM) was compared with the ROM of the unaffected limbs and the control patients. There were no statistically significant differences in ROM between the two groups except for fixed pronation deformity of the synostosis (p = 0.0133). The average ABILHAND-Kids score for all children was 38.625 ± 3.021, close to the average score of 42. Only one patient with bilateral involvement underwent surgical correction of the deformity 5 years from the initial presentation.Conclusion CRUS is a rare congenital condition that can affect daily living activities. Surgical correction is rarely indicated and is only preserved for patients with bilateral involvement and significant functional impairment.
Keywords: congenital; radioulnar synostosis; management; functional outcome; forearm deformity